2005
DOI: 10.1517/17425255.1.3.409
|View full text |Cite
|
Sign up to set email alerts
|

Use ofin vitrotransporter assays to understand hepatic and renal disposition of new drug candidates

Abstract: Hepatic and renal transporters contribute to the uptake, secretion and reabsorption of endogenous compounds, xenobiotics and their metabolites and have been implicated in drug-drug interactions and toxicities. Characterising the renal and hepatic disposition of drug candidates early in development would lead to more rational drug design, as chemotypes with 'ideal' pharmacokinetic characteristics could be identified and further refined. Because transporters are often organ specific, 'custom' transporter panels … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 191 publications
2
17
0
Order By: Relevance
“…Thus, the in vivo excreta results showed that degarelix is mainly excreted unchanged via the urine and is subject to extensive sequential peptidic degradation during its elimination via the hepato-biliary pathway. The results are in line with data for other compounds of similar size and structure as degarelix and in line with the fact that compounds of this size (molecular weight, 1632 Da) are more likely to be eliminated by the hepato-biliary pathway (Sahi, 2005).…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Thus, the in vivo excreta results showed that degarelix is mainly excreted unchanged via the urine and is subject to extensive sequential peptidic degradation during its elimination via the hepato-biliary pathway. The results are in line with data for other compounds of similar size and structure as degarelix and in line with the fact that compounds of this size (molecular weight, 1632 Da) are more likely to be eliminated by the hepato-biliary pathway (Sahi, 2005).…”
Section: Discussionsupporting
confidence: 87%
“…Because degarelix has been shown not to induce CYP3A4 in vitro, no further tests of P-glycoprotein induction , our data show that degarelix is highly unlikely to cause any drug interaction with coadministrated drugs when used for the treatment of patients with prostate cancer. Similar to other peptide drugs of this size (Sahi, 2005), degarelix is subject to proteolysis by endopeptidases, and unchanged degarelix and its metabolites are fully excreted via the hepatic and urinary pathway. Therefore, systemic exposure to any metabolic products also seems to be low and/or negligible.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the free fraction of drug in plasma and dose (in particular if Ͼ100 mg) are other important parameters to consider when evaluating the need for a clinical drug interaction study. As discussed in the FDA Guidance and in the review by Sahi (2005), drug-drug interaction potential can be estimated using [I]/K i , where I is inhibitor concentration and K i is the inhibition constant (note that use of total concentration is recommended in the FDA Guidance because this provides the most conservative estimate). If the [I]/K i ratio is Ͻ0.02, the chance of an interaction is remote.…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence to suggest that AO contributes to the pharmacokinetic interaction between zaleplon and cimetidine (Renwick et al, 2002); however, cimetidine is known to inhibit P450 enzymes and renal organic anion and cation transporters (Somogyi, 1996;Sahi, 2005), so the specific contribution of AO to the observed DDI is not known. Recently, a group of scientists, under the auspices of the Drug Metabolism Leadership Group of the Innovation and Quality Consortium, conducted an evaluation of having a metabolite as the sole contributor to P450 inhibition-based DDIs.…”
Section: )mentioning
confidence: 99%